2012
DOI: 10.3390/f3040903
|View full text |Cite
|
Sign up to set email alerts
|

The Sign and Strength of Plant-Soil Feedback for the Invasive Shrub, Lonicera maackii, Varies in Different Soils

Abstract: Plants alter soil characteristics causing changes in their subsequent growth resulting in positive or negative feedback on both their own fitness and that of other plants. In a greenhouse study, we investigated whether the sign and strength of feedback changed across two distinct soil types, and whether effects were due to shifts in biotic or abiotic soil traits. Using soils from two different locations, we examined growth of the exotic invasive shrub, Lonicera maackii and the related native shrub, Diervilla l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…While there is some evidence to suggest that soil type and nutrient availability may influence the sign and magnitude of feedbacks (Manning et al 2008;Schradin and Cipollini 2012), the influence of forest fire is relatively unknown. Despite the obvious effects of forest fire (e.g., removal of aboveground vegetation and nutrient release), fire may also influence soil communities (Dooley and Treseder 2012;Xiang et al 2014Xiang et al , 2015.…”
mentioning
confidence: 99%
“…While there is some evidence to suggest that soil type and nutrient availability may influence the sign and magnitude of feedbacks (Manning et al 2008;Schradin and Cipollini 2012), the influence of forest fire is relatively unknown. Despite the obvious effects of forest fire (e.g., removal of aboveground vegetation and nutrient release), fire may also influence soil communities (Dooley and Treseder 2012;Xiang et al 2014Xiang et al , 2015.…”
mentioning
confidence: 99%
“…Iannone et al (2015) also found higher pH in soil invaded by common buckthorn (Rhamnus cathartica L.), but concluded that this difference was related to preexisting conditions. Supporting the idea that honeysuckle was responsible for increased soil pH, Schradin and Cipollini (2012) determined that honeysuckle increased soil pH in greenhouse experiments.…”
Section: Resultsmentioning
confidence: 91%
“…, Mangla et al. , Schradin and Cipollini ), enhance their own species performance (Klironomos , Callaway et al. , Felker‐Quinn et al.…”
Section: Introductionmentioning
confidence: 99%
“…, ), and plant–soil interactions of these shrubs singly can promote other nonnative species (Kuebbing et al. ) or suppress native species (Gorchov and Trisel , Schradin and Cipollini ). However, the relative impact of each invasive shrub individually may differ depending on species‐specific plant–soil interactions (Shannon et al.…”
Section: Introductionmentioning
confidence: 99%